ABO(H) blood groups and pre-eclampsia - Clark, Peter; Wu, Olivia (Thrombosis and Haemostasis, 2008)
pre-eclampsia is associated with both placental thrombosis and thrombophilia. The ABO(H) blood group influences von Willebrand factor, which is a risk factor for arterial and venous thrombosis. Over many years a number of studies have examined the relationship between ABO(H) and pre-eclampsia, but no consensus exists as to whether there is a true association. Correspondingly, a systematic review of studies reporting an association between ABO(H) blood group and pre-eclampsia syndromes was performed. From the 17 eligible studies there was no consistent link between blood group AB and pre-eclampsia, with a pooled odds ratio of group AB versus the remainder of 1.02 (95%CI 0.86 to 1.22).There was no evidence of heterogeneity and individual study estimates were relatively consistent. Comparing a combined group of non-Os (i.e.AA, AB and BB) with group O gave similar results, with a pooled odds ratio of 1.01 (95%CI 0.91 to 1.12), but with some evidence of heterogeneity (p=0.01) and individual study estimate inconsistency (I2 49%).However, no specific feature (disease definition, disease severity, date of publication, or ABO(H) distribution in controls) distinguished those few studies giving any form of positive association from the remainder. In summary, no clear association between any ABO(H) blood group and pre-eclampsia can be made from available studies. However, existing data does not allow exclusion of an effect limited to those expressing the least O(H) antigen.
Keywords: ABO(H) blood groups; pre-eclampsia; systematic review